ANTIMONY-DOPED TIN(IV) OXIDE - SURFACE-COMPOSITION AND ELECTRONIC-STRUCTURE - Egdell, R; Flavell, W; Tavener, P (1984)
Antimony-doped tin(IV) oxide Sn1-xSbxO2 prepared by a high-temperature (1300 K) solid-state synthetic procedure has been studied over the composition range0 < x < 0.03by X-ray and ultraviolet photoelectron spectroscopy (XPS and UPS) and high-resolution electron-energy-loss spectroscopy (HREELS). Pronounced enrichment by antimony close to the surface is evident from XPS with a heat of segregation approaching 30 kJ/mole. However, no increase in the surface free-carrier concentration is evident from the conduction-to-valence band intensity ratio in UPS or from the surface plasmon frequency in EELS. It is concluded that electrons associated with segregated Sb ions occupy a lone-pair-likesp hybrid surface state whose energy lies well below that of the conduction band. © 1984 Academic Press, Inc.